Optimasi Produksi Kitosan Larut Air menggunakan Metode Hidrolisis Bertekanan: Optimatization of Production Water Soluble Chitosan Using Pressurized Hidrolysis Method - Sudianto; Sugeng Heri Suseno; Pipih Suptijah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Modifications for chitosan production continue to be done so as to produce various forms of chitosan in the form of chips, granules, membranes and gels. Meanwhile, to diversify the derivatives from chitosan still needs to be done, existing chitosan diversified products such as glucosamine and water soluble chitosan production needs to be done to increase diversification and expand the use of chitosan products. The purpose of this study was to determine the optimum conditions of the water soluble chitosan production process by hydrolysis pressure using the Box-Behnken Methodology Response Surface (RSM-BoxBehnken) with Design Expert 07.0.0 program software. The RSM-Box Behnken recommends optimum conditions for production of water soluble chitosan at 1.75% HCl concentration, 1:10 ratio fo chitosan, for 45 minutes (desirability 76.1%) resulting in yield of 79,5%, pH of 5,93, water content of 25.45% , ash content of 1.33%, nitrogen level of 4.78% and solubility of chitosan of 42.66%. Processing production water soluble chitosan using the optimum conditions from the RSM recommendation obtained yield of 80%, pH of 6.0, water content of 41.9% , ash content of 1.29%, nitrogen level of 3.28% and solubility of chitosan of 66.38%.